Endoplasmic reticulum-associated protein degradation contributes to Toll innate immune defense in Drosophila melanogaster - Zhu, Yangyang; Liu, Lei; Zhang, Chuchu; Zhang, Chao; Han, Tingting; Duan, Renjie; Jin, Yiheng; Guo, Huimin; She, Kan; Xiao, Yihua; Goto, Akira; Cai, Qingshuang; et al. (Frontiers in Immunology, 2023)
In Drosophila, the endoplasmic reticulum-associated protein degradation (ERAD) is engaged in regulating pleiotropic biological processes, with regard to retinal degeneration, intestinal homeostasis, and organismal development. The extent to which it functions in controlling the fly innate immune defense, however, remains largely unknown. Here, we show that blockade of the ERAD in fat bodies antagonizes the Toll but not the IMD innate immune defense in Drosophila. Genetic approaches further suggest a functional role of Me31B in the ERAD-mediated fly innate immunity. Moreover, we provide evidence that silence of Xbp1 other than PERK or Atf6 partially rescues the immune defects by the dysregulated ERAD in fat bodies. Collectively, our study uncovers an essential function of the ERAD in mediating the Toll innate immune reaction in Drosophila